Study of sauce glazed wares from Yaozhou kilns (Northern Song Dynasty, 960–1127 CE): Probing the morphology and structure of crystals in the glazes. Issue 15 (December 2022) - Ren, Zhao; Wang, Fen; Hole, Clement; Sciau, Philippe; Shi, Pei; Zhu, Jianfeng; Luo, Hongjie; Li, Qiang; Wang, Tian
Abstract: Sauce glaze is one of the main varieties of glazes produced in the Yaozhou kilns during the Song Dynasty. It is famous for its reddish-brown color and high gloss. In this work, the elemental composition, morphology, structure, and light reflectivity of glazes of archeological sherds were systematically studied. A large number of ε-Fe2 O3 dendritic crystals were observed in the glazes. Alkali etching was implemented to remove the glassy matrix surrounding these crystals to further investigate their microstructure. SEM observations emphasize that they are composed of well-arranged parallel branches separated by about 230 nm, each of which consisting of offset stacks of many small flake-shaped crystals, with the offset ranging from 100 to 110 nm. Based on these results, the origin of the reddish-brown color and high gloss was discussed. In addition, cordierite crystals were observed for the first time in the sauce glaze from Yaozhou kilns.